The Application of Diffusion Kurtosis Imaging on the Heterogeneous White Matter in Relapsing-Remitting Multiple Sclerosis - Zhu, Qiyuan; Zheng, Qiao; Luo, Dan; Peng, Yuling; Yan, Zichun; Wang, Xiaohua; Chen, Xiaoya; Li, Yongmei (Frontiers in Neuroscience, 2022)
Objectives: To evaluate the microstructural damage in the heterogeneity of different white matter areas in relapsing-remitting multiple sclerosis (RRMS) patients by using diffusion kurtosis imaging (DKI) and its correlation with clinical and cognitive status. Materials and Methods: Kurtosis fractional anisotropy (KFA), fractional anisotropy (FA), mean kurtosis (MK) and mean diffusivity (MD) in T1-hypointense lesions (T1Ls), pure T2-hyperintense lesions (pure-T2Ls), normal-appearing white matter (NAWM) and white matter in healthy controls (WM in HCs) were measured in 48 RRMS patients and 26 sex- and age- matched HCs. All the participants were assessed with the Mini-Mental State Examination (MMSE), the Montreal Cognitive Assessment (MoCA) and the Symbol Digit Modalities Test (SDMT) scores as the cognitive status. The Kurtzke Expanded Disability Status Scale (EDSS) scores were used to evaluate the clinical status in RRMS patients. Results: The lowest KFA, FA and MK values and the highest MD values were found in T1Ls, followed by pure-T2Ls, NAWM and WM in HCs. The T1Ls and pure-T2Ls were significantly different in FA (p = 0.002) and MK (p = 0.010), while the NAWM and WM in HCs were significantly different in KFA, FA and MK (p < 0.001). The KFA, FA, MK and MD values in NAWM (r = 0.349, p = 0.017; r = 0.410, p = 0.005; r = 0.372, p = 0.011; r = -0.514, p < 0.001) were correlated with the MMSE scores and the FA, MK and MD values in NAWM (r = 0.424, p = 0.003; r = 0.424, p = 0.003; r = -0.368, p = 0.012) were correlated with the SDMT scores. Conclusion: Applying DKI to the imaging-based white matter classification has the potential to reflect the white matter damage and is well correlated with the disease severity.